Finanční deriváty - alternativa portfolia - Makovský, Zdeněk; Tetřevová, Liběna (Univerzita Pardubice, 2009)
The article deals with the problems of financial derivatives as an alternative of portfolio in conditions of Prague Stock Exchange. Firstly, attention is paid to financial derivatives which represent financial instruments whose value depends on, or are derived from, the price of other underlying variables. Secondly, the problems of diversification and creation of optimal portfolio are mentioned. Problems of securities and derivatives traded on the Prague Stock Exchange are characterized as well. Then, transaction cost, leverage effect and dividends as factors of investor’s decision making are discussed. Attention is focused especially to futures contract and index futures.
Keywords: Risks; leverage effect; diversification; portfolio; financial derivatives; indexes; futures